Are foreign correspondents redundant? - Sambrook, R (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford, 2010)
International news reporting is undergoing a profound transformation. Western newspapers and broadcasters have steadily cut back on foreign correspondents and reporting over the last 20 years in the face of economic pressures. Now technology and cultural changes brought by globalisation are bringing additional pressures to news organisations and the internet has also allowed new voices to be heard. News organisations are having to adapt and redefine themselves in the face of turbulent changes to how we learn about the world. Richard Sambrook has been closely involved in reporting international news for 30 years. Here he analyses the changes underway and points towards fresh ways of reporting the world.